2011
DOI: 10.4061/2011/708750
|View full text |Cite
|
Sign up to set email alerts
|

Multiple Sclerosis: Are Protective Immune Mechanisms Compromised by a Complex Infectious Background?

Abstract: The immunological background of multiple sclerosis (MS) manifests as an altered reactivity against a diverse range of infections, particularly with the Epstein-Barr virus. Although this could be only an epiphenomenon of a more generalised dysfunction of the immune system in MS, it is also possible that a complex infectious background forms the basis of a specific immune dysregulation finally causing the disease. It is thus suggested that the complex infectious background bears the key for an understanding of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 89 publications
0
12
0
Order By: Relevance
“…HERV has been isolated from CSF, serum and plasma of the patients with MS (18, 30). In this respect it is of interest that the presence of HERV sequences, and in particular those of the γ-retroviruses HERV-W/MSRV and of HERV-H/F, have ben found in association with MS (31,32). In addition increased levels of antibody reactivity to specific γ-retroviral HERV Gag and Env epitopes have been found in serum and CSF from MS patients (19).…”
Section: Discussionmentioning
confidence: 99%
“…HERV has been isolated from CSF, serum and plasma of the patients with MS (18, 30). In this respect it is of interest that the presence of HERV sequences, and in particular those of the γ-retroviruses HERV-W/MSRV and of HERV-H/F, have ben found in association with MS (31,32). In addition increased levels of antibody reactivity to specific γ-retroviral HERV Gag and Env epitopes have been found in serum and CSF from MS patients (19).…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, most of the infectious agents that are putatively associated with MS are ubiquitous and infect most humans at some point in their lives [111]. With regards to the infectious agents discussed above, it was found that, in one study, >50% of the MS patients showed serological evidence of prior infection with Mycoplasma pneumoniae [31].…”
Section: Discussionmentioning
confidence: 99%
“…The extent of interplay between these different factors is under rigorous investigation. The heterogeneity of the disease might also suggest that MS is not caused or triggered by only one virus, but rather a more complex set of viral infections could act as triggers in genetically susceptible individuals [3]. Some of the questions that need to be explored include the extent of the interplay between MS risk genes, vitamin D levels, UV-light exposure, tobacco smoking and viruses- are there risk factors that when present can amplify the risk of MS or are all these risk factors independent?…”
Section: Introductionmentioning
confidence: 99%